RESPONSE OF RUSSIAN AIR CARRIERS IN THE FIGHT FOR THE CARBON MARKET - Yu. V. Smirnova (Научный вестник МГТУ ГА, 2016)
The article discusses the consequences associated with failure of domestic airlines to participate in the existing market of emissions trading. The carbon market was approved by the European Union. Who insisted on taking its trade in the carbon market. Europe is insisting that the airlines pay for their flights over its territory. The article shows what steps Russia is taking to establish its system of accounting for greenhouse gas emissions and measures to reduce them under "climate harmonization".